A place to find oneself. Displacements and rituals among Guarani People from Paraguayan Chaco - Dominguez, Maria Eugenia (Revista de Antropologia, 2020)
As already established in ethnological literature, Chaco War (Bolivia-Paraguay, 1932-1935) launched a range of spatial displacements that reshaped the local ethnic map. This paper sketches out the displacements that took the guarani and isosenho people from Bolivia to northern paraguaian Chaco, and then describes the formation of the five communities established in this area. Secondly, it refers to guarani sociality by examining the role of ritual in their history and social life. Through a performative approach to ritual and indigenous art practices, the paper argues that in this context, ritual acts as a powerful means to build chacoan space as a guarani place.